A gel-assisted non-destructive treatment method for PBO fiber surface

Through gel assisted technology, PBO fibers are subjected to lossless sizing using reactive functionalized POSS sizing agent and POSS gel factor, which solves the problem of poor surface treatment effect of PBO fibers, improves its surface energy and bonding strength with resin, and expands the application range of composite materials.

CN116005457BActive Publication Date: 2025-05-02ZHEJIANG UNIV OF TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202211656681.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-22
Publication Date
2025-05-02
Estimated Expiration
2042-12-22

AI Technical Summary

Technical Problem

The prior art is difficult to effectively treat the PBO fiber surface, resulting in poor compatibility with the resin matrix, limiting the application range of PBO fiber-reinforced resin-based composite materials.

Method used

Using a gel-assisted method, the PBO fiber is subjected to non-destructive sizing treatment by synthesizing reactive functionalized POSS sizing agent and POSS gel factor, thereby improving its surfactivity and interface binding force with the resin.

Benefits of technology

It realizes efficient treatment of the PBO fiber surface, improves its surface energy and bonding strength with the resin matrix, and expands the application range of PBO fiber-reinforced resin-based composite materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004011728940000051
    Figure BDA0004011728940000051
  • Figure BDA0004011728940000061
    Figure BDA0004011728940000061
  • Figure BDA0004011728940000141
    Figure BDA0004011728940000141
Patent Text Reader

Abstract

The present invention provides a gel-assisted non-destructive treatment method for the surface of PBO fibers, comprising: preparing reactive functionalized POSS; preparing POSS gel factor; performing sizing treatment on the PBO fibers by gel-assisted technology: dissolving the POSS gel factor in a solvent, heating to 100-140° C., adding reactive functionalized POSS and mixing evenly to form a sol, namely, a reactive functionalized POSS sizing agent; cooling the reactive functionalized POSS sizing agent to 80° C. to 40° C., and performing immersion sizing treatment on the PBO fibers. The present invention synthesizes a reactive functionalized PBO fiber sizing agent based on a POSS structure, and performs gel-assisted non-destructive sizing treatment on the surface of the PBO fibers to improve the combination of the PBO fibers with a resin matrix, thereby expanding the application range of PBO fiber-reinforced resin-based composite materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of non-destructive treatment of PBO fiber surfaces, and in particular to a gel-assisted non-destructive treatment method for PBO fiber surfaces. Background Art

[0002] PBO fiber is the abbreviation of poly(p-phenylene benzobisoxazole) fiber. Its main chain contains a rigid rod-like molecular structure composed of benzene rings and aromatic heterocyclic rings, as well as a highly oriented ordered structure formed when the molecular chain is spun in a liquid crystal state. Therefore, it has the characteristics of high strength, high modulus, high temperature resistance, flame retardancy, etc., and its comprehensive performance is the best among all "organic fibers". Due to its excellent comprehensive performance, PBO fiber is widely used in many industrial fields such as aerospace, national defense and military industry. Due to its high molecular weight, narrow molecular weight distribution, high crystallinity and chain segment orientation, the surface of PBO fiber is extremely dense, smooth, and has high chemical inertness, which makes the compatibility between PBO fiber and the resin matrix interface poor, resulting in the design, manufacture and application of PBO fiber-reinforced resin-based composite materials being greatly restricted.

[0003] The existing surface treatment methods for PBO fibers include chemical oxidation, surface chemical grafting, electrochemical oxidation, plasma treatment, and high-energy ray irradiation. Among them, surface chemical grafting is the most widely used surface treatment method for PBO fibers, which mainly includes polymer coating, nanoparticle coating, surface gradient structure construction, etc. The traditional surface sizing treatment method uses a large amount of low-viscosity solvents, such as a PBO fiber sizing agent containing a benzoxazole diamine compatibilizer disclosed in the patent with publication number CN112760972A and its application, and a benzoxazole ion compound and a PBO fiber emulsion sizing agent containing the compound disclosed in the patent with publication number CN111825696B and its preparation method, etc., and the one-time sizing effect is not good, and multiple treatments are often required to achieve the ideal sizing effect. Therefore, it is of application value to develop a sizing method that can efficiently treat the surface of PBO fibers and form a long-term stable effect.

[0004] Polyhedral oligomeric silsesquioxane (POSS) is a novel organic-inorganic hybrid material, and its internal inorganic framework is a hexahedral cage structure composed of Si-O-Si bonds, which has good structural symmetry, and its exterior can carry a variety of organic groups (R groups) on each Si atom to extend outward. The R group terminal can be H and active or inactive groups, such as epoxy, amino, carboxyl, alkenyl, alkyl, hydroxyl, aryl, etc. The introduction of variable R groups makes POSS have good reactivity and compatibility. Due to its special nanostructure, nanometer size effect, crosslinking effect, etc., POSS is often used as a polymer modified material. As disclosed in the patent publication number CN102634976A, the method for surface deposition (POSS / TiO2)n film enhancing the UV resistance stability of PBO fiber is deposited on the PBO fiber surface to increase the roughness of the fiber surface and the bonding force with the resin interface. Therefore, using functionalized POSS as a sizing agent molecule can improve the surface activity and surface roughness of PBO fibers and improve the interfacial bonding between fibers and resins. At the same time, POSS with a specific structure can act as a gel factor, aggregate and self-assemble in a liquid medium to form extended fibrous aggregates, and further restrict the flow of liquid molecules to form a gel (Chem. Commun., 2014, 50, 718). Therefore, using POSS gel factor to gel the solvent used for sizing and then assist sizing can reduce the amount of solvent used and the sizing effect. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a gel-assisted non-destructive treatment method for the surface of PBO fibers, by performing gel-assisted non-destructive sizing treatment on the surface of PBO fibers, thereby improving the bonding between the PBO fibers and the resin matrix and expanding the application range of PBO fiber-reinforced resin-based composite materials.

[0006] The present invention innovatively provides a gel-assisted PBO fiber surface non-destructive treatment technology, synthesizes a reactive functionalized PBO fiber sizing agent based on a POSS structure, and uses the gel-assisted technology to perform non-destructive treatment on the PBO fiber.

[0007] In order to achieve the above-mentioned purpose, the gel-assisted non-destructive treatment technology for the surface of PBO fibers of the present invention first synthesizes a reactive functionalized POSS sizing agent, utilizes the chemical bonding between the four active R groups of POSS and different polymer matrices, and the other four active R groups are combined with the surface of the PBO fibers; secondly, synthesizes the POSS gel factor; finally, the PBO fibers are sized by gel-assisted technology. The composition and weight parts of the reactive functionalized sizing agent are as follows:

[0008] 85-95 parts of solvent;

[0009] Reactive functionalized POSS 5-10 parts;

[0010] POSS gel factor 0.5-5 parts.

[0011] A gel-assisted PBO fiber surface non-destructive treatment method comprises the following steps:

[0012] (1) Preparation of reactive functionalized POSS:

[0013] (2) Preparation of POSS gel factor:

[0014] (3) Sizing of PBO fibers by gel-assisted technology:

[0015] 3.1): Dissolve the POSS gel factor in a solvent, heat to 100-140° C., add the reactive functionalized POSS and mix evenly to form a sol, which is a reactive functionalized POSS sizing agent;

[0016] 3.2): The reactive functionalized POSS sizing agent is cooled to 80°C to 40°C, and the PBO fiber is immersed in the sizing treatment.

[0017] In step (1), preparing reactive functionalized POSS specifically comprises:

[0018] 1.1): Graft 1 and graft 2 are mixed in a ratio of 4:4-2:6 under an ice bath, and then condensation reagents 1-hydroxybenzotriazole and benzotriazole-N,N,N',N'-tetramethyluronium hexafluorophosphate are added, and N-methylmorpholine is added as an acid binding agent, and then a POSS derivative is added. The reaction is continued for 18 to 30 hours and then stopped. After the reaction is completed, POSS-1 is obtained by post-treatment;

[0019] 1.2): POSS-1 was dissolved in chloroform, and then grafted material 3 and triethylamine were added to synthesize terminal benzoxazolyl-modified POSS-2 molecules through thiol-double bond click reaction. After the reaction, the solvent was removed by rotary evaporation, and the reactive functionalized POSS was obtained after vacuum drying.

[0020] In step 1.1), post-processing includes:

[0021] The yellow solution obtained after the reaction is completed is poured into a citric acid aqueous solution, and a white precipitate is generated after mixing. The white precipitate is obtained by suction filtration. The precipitate is washed with methanol, suction filtered, and dried to obtain POSS-1.

[0022] In step 1.1), the grafted substance 1 is at least one of succinic acid, glutaric acid, terephthalic acid, isophthalic acid, furandicarboxylic acid, adipic acid, sebacic acid, and suberic acid;

[0023] The grafted substance 2 is at least one of 5-hexenoic acid, 2-methyl-4-pentenoic acid, 4-pentenoic acid, 6-heptenoic acid, 7-octenoic acid, 8-nonenoic acid and 9-decenoic acid.

[0024] In step 1.1), the POSS derivative is octa-aminopropyl POSS hydrochloride, γ-glycidyloxysilylpropyl POSS, octavinyl-POSS or octachloropropyl silsesquioxane.

[0025] In step 1.2), the grafted compound 3 is 2-mercaptobenzoxazole, 5-methoxybenzoxazole-2-thiol or 5-chloro-2-mercaptobenzoxazole.

[0026] In step (2), prepare POSS gel factor, specifically comprising:

[0027] 2.1): (S)-2,6-di-tert-butoxycarbonylaminocaproic acid is dissolved in N,N-dimethylformamide, then N-methylmorpholine is added, and a mixture of carbodiimide and 1-hydroxybenzotriazole is added under ice bath;

[0028] 2.2): After activation for 20 to 40 minutes, add POSS amino hydrochloride, gradually raise the temperature to 15 to 35°C, and continue the reaction for 16 to 30 hours;

[0029] 2.3): After the reaction is completed, a yellow solution is obtained, and the yellow solution is poured into a citric acid-water solution. After the two are mixed, a white precipitate is generated. The white precipitate is post-treated to obtain a POSS gel factor.

[0030] In step 2.2), the POSS amino hydrochloride is octa-aminopropyl POSS hydrochloride.

[0031] In step 2.3), the post-processing includes:

[0032] The white precipitate was washed with acetonitrile and purified by chromatography to obtain the product POSS gel factor.

[0033] In step 3.1), the mixture is heated to 110-130° C. and reactive functionalized POSS is added and mixed uniformly to form a sol.

[0034] Specifically, (1) the reactive functionalized POSS is realized by the following technical scheme:

[0035] Step 1: Mix graft 1 and graft 2 in a ratio of 4:4-2:6 under an ice bath, then add condensation reagents 1-hydroxybenzotriazole (HOBT) and benzotriazole-N,N,N',N'-tetramethyluronium hexafluorophosphate (HBTU), and add N-methylmorpholine (NMM) as an acid binding agent. Add the POSS derivative after 30 minutes. The reaction gradually returns to room temperature and stops after 24 hours. After the reaction is completed, the yellow solution obtained by the reaction is poured into a citric acid aqueous solution, and a white precipitate is generated after mixing. The white precipitate is obtained by suction filtration with a Buchner funnel, and the precipitate is washed 3 times with methanol, suction filtered, and dried to obtain POSS-1 with an appearance of white powder or transparent oil.

[0036] Step 2: A certain amount of POSS-1 is dissolved in chloroform, and then 0.5eq of grafted product 3 and a certain amount of triethylamine are added to synthesize terminal benzoxazolyl POSS-2 molecules through thiol-double bond click reaction. After the reaction is completed, the solvent is removed by rotary evaporation, and after vacuum drying, a reactive functionalized POSS-2 sizing agent molecule with a light yellow powder or yellow transparent oil is obtained.

[0037] The grafted substance 1 is glycidyl acrylate, 3-(allyloxy)oxetane, β-phenylacrylic acid, m-methoxybenzoic acid, p-hydroxybenzoic acid, aniline and the like.

[0038] The grafted substance 2 is 5-hexenoic acid, 2-methyl-4-pentenoic acid, 4-pentenoic acid, 6-heptenoic acid, 7-octenoic acid, 8-nonenoic acid, 9-decenoic acid and the like.

[0039] The grafted compound 3 is 2-mercaptobenzoxazole, 5-methoxybenzoxazole-2-thiol, 5-chloro-2-mercaptobenzoxazole, and the like.

[0040] The POSS derivative is octa-aminopropyl POSS (OAS) hydrochloride (POSS-NH3 + Cl-), γ-glycidyloxysilylpropyl POSS, octavinyl-POSS or octachloropropylsilsesquioxane (OCP-POSS).

[0041] (2) POSS gel factor is prepared by the following steps:

[0042] Step 1: Dissolve (S)-2,6-di-tert-butoxycarbonylaminocaproic acid (BOC-Lys(BOC)-OH) in N,N-dimethylformamide (DMF), then add N-methylmorpholine (NMM). Add a mixture of carbodiimide (EDCI) and 1-hydroxybenzotriazole (HOBT) in an ice bath.

[0043] Step 2: After activation for 30 min, add POSS amino hydrochloride. Gradually warm the reaction to room temperature and continue the reaction for 24 h.

[0044] Step 3: After the reaction is completed, a yellow solution is obtained, which is poured into a citric acid-water solution. A white precipitate is produced after the two are mixed. The white precipitate is obtained by filtering with a Buchner funnel, washing the white precipitate with acetonitrile, and then purified by a chromatographic column. The obtained product POSS gel factor has a white crystalline appearance. The POSS gel factor is octa-aminopropyl POSS (OAS) hydrochloride (POSS-NH3 + Cl-) as the core, and the dendrimer is formed by condensation polymerization. Its grafted products are lysine or cystine derivatives such as Boc-Cys(Me)-OH, Boc-Cys(Fm)-OH, N-Boc-S-benzyl-L-cysteine, S-acetamidomethyl-N-tert-butyloxycarbonyl-L-cysteine, Boc-S-tert-butylmercapto-L-cysteine, Boc-Lys(Me)2-OH, Boc-Lys(Boc)-Pro-OH, and Boc-Lys(Boc)-Pro-OH.

[0045] The reaction equation is as follows:

[0046]

[0047]

[0048] (3) The method for sizing PBO fibers by gel-assisted technology is as follows:

[0049] Step 1: dissolve the POSS gel factor in a solvent, heat to 120° C., add the reactive functionalized POSS and mix evenly to form a sol, which is the reactive functionalized POSS sizing agent.

[0050] Step 2: Cool the reactive functionalized POSS sizing agent to 80° C. to 40° C., and perform immersion sizing treatment on the PBO fiber.

[0051] Step 3: Drying the treated PBO fiber at 25°C to 40°C.

[0052] Compared with the prior art, the present invention has the following advantages:

[0053] The gel-assisted sizing agent prepared by the present invention can effectively treat the surface of PBO fiber and form a long-term stable effect, which can improve the surface energy of PBO fiber and the bonding strength with the resin matrix. The gel has a relatively low viscosity in the sol state, which is helpful for the fiber sizing treatment. After the gel is cooled, the viscosity rises suddenly, which can make the sizing agent adhere to the fiber for a long time, provide a good reaction environment, reduce the number of dipping times, and improve the PBO treatment efficiency. In addition, the sizing agent involved in the present invention is a dendritic macromolecule, which has sufficient reactive sites, can react with the resin and the fiber, and enhance the coupling effect between the resin and the fiber. DETAILED DESCRIPTION

[0054] The present invention will be further described below in conjunction with specific implementation examples.

[0055] Embodiment 1:

[0056] (1) Reactive functionalized POSS synthesis:

[0057] Step 1: Evenly mix 33g (0.28moL) of succinic acid and 32g (0.28moL) of 5-hexenoic acid in an ice bath, then add 110g (0.80moL) of 1-hydroxybenzotriazole (HOBT) and 290g (0.8moL) of benzotriazole-N,N,N',N'-tetramethyluronium hexafluorophosphate (HBTU), and add 150g (1.5moL) of N-methylmorpholine (NMM). After 30min, add 60g (0.07moL) of octa-aminopropyl POSS (OAS) hydrochloride. The reaction gradually returns to room temperature and stops after 24h. After the reaction is completed, the yellow solution obtained by the reaction is poured into 1000mL (0.50M) of citric acid aqueous solution, and a white precipitate is produced after mixing. The white precipitate was filtered out with a Buchner funnel, and the precipitate was washed three times with 500 mL of methanol, filtered out, and dried to obtain POSS-1 in the form of white powder or transparent oil. 1 H NMR) characterization confirmed that it was consistent with the design, δH(DMSO-d6) = 0.56, 1.51, 1.79, 2.16, 2.34, 2.42, 2.61, 3.41, 4.88, 5.13, 5.82, 12.18 ppm. The peak area integration at δH = 5.82 and 2.84 ppm was about 1:1, which showed that the grafting ratio of succinic acid to 5-hexenoic acid was 1:1.

[0058] Step 2: Dissolve a certain amount of POSS-1 in chloroform, then add 42g (0.28 mol) of 2-mercaptobenzoxazole and a certain amount of triethylamine, and synthesize the terminal benzoxazole POSS-2 molecule through the thiol-double bond click reaction. After the reaction is completed, the solvent is removed by rotary evaporation, and the reactive functionalized POSS-2 sizing agent molecule with the appearance of light yellow powder or yellow transparent oil is obtained by vacuum drying. The synthesized structure POSS-2 was confirmed by nuclear magnetic resonance ( 1 H NMR) characterization confirmed that the peaks representing double bonds at δH(DMSO-d6)=4.88, 5.13, and 5.82 ppm disappeared, indicating that the reaction was complete and all double bonds were reacted.

[0059] (2) Synthesis of POSS gel factor:

[0060] 236g (0.68mol) (S)-2,6-di-tert-butoxycarbonylaminocaproic acid (BOC-Lys(BOC)-OH) was dissolved in 2000mL N,N-dimethylformamide (DMF), and then 139g (1.36mol) N-methylmorpholine (NMM) was added. A mixture of 144g (0.68mol) carbodiimide (EDCI) and 101g (0.75mol) 1-hydroxybenzotriazole (HOBT) was added under ice bath. After activation for 30min, 50g (0.043mol) POSS amino hydrochloride was added. The reaction was gradually warmed to room temperature and the reaction lasted for 24h. After the reaction was completed, a yellow solution was obtained, which was poured into 1000mL (0.50mol / L) of citric acid-water solution, and a white precipitate was produced after the two were mixed. The white precipitate was obtained by filtering with a Buchner funnel, and the white precipitate was washed with acetonitrile and purified by a chromatographic column. The stationary phase of the silica gel column is 200-300 mesh silica gel, and the mobile phase is a mixed solvent of dichloromethane / methanol with a volume ratio of 15:1. The obtained product POSS gel factor has a white crystalline appearance. δH(DMSO-d6)=7.74,6.70,6.36,3.79,2.99,2.83,1.54-1.39,1.25-1.40,0.52ppm. FTIR(KBr)v=3341,2985,2932,1690,1517,1372,1109cm -1 m / z (ESI-MS): [M+H+Na] / 2 The theoretical value is 1765.4, and the measured value is 1765.4. The measured value is consistent with the theoretical value, proving that the structure of the obtained product is consistent with the designed structure.

[0061] (3) PBO fiber sizing treatment:

[0062] 10g of POSS gel factor was dissolved in 1000mL of chloroform solvent, heated to 120°C, and 100g of reactive functionalized POSS-2 sizing agent molecules were added and mixed evenly to form a sol, which was a reactive functionalized POSS sizing agent. The reactive functionalized POSS sizing agent was cooled to 80°C, and the PBO fiber was immersed and sized. The treated PBO fiber was dried at 40°C.

[0063] Embodiment 2:

[0064] (1) Reactive functionalized POSS synthesis:

[0065] Step 1: Evenly mix 46.5g (0.28moL) of terephthalic acid and 32g (0.28moL) of 5-hexenoic acid in an ice bath, then add 110g (0.80moL) of 1-hydroxybenzotriazole (HOBT) and 290g (0.80moL) of benzotriazole-N,N,N',N'-tetramethyluronium hexafluorophosphate (HBTU), and add 150g (1.50moL) of N-methylmorpholine (NMM). After 30min, add 60g (0.07moL) of octa-aminopropyl POSS (OAS) hydrochloride. The reaction gradually returns to room temperature and stops after 24h. After the reaction is completed, the yellow solution obtained by the reaction is poured into 1000mL (0.50M) of citric acid aqueous solution, and a white precipitate is generated after mixing. The white precipitate was filtered out with a Buchner funnel, and the precipitate was washed three times with 500 mL of methanol, filtered out, and dried to obtain POSS-1 in the form of white powder or transparent oil. 1 H NMR) characterization confirmed that it was consistent with the design, δH(DMSO-d6) = 0.56, 1.51, 1.79, 2.16, 2.34, 2.84, 3.41, 4.88, 5.13, 5.82, 8.06, 8.2112.17 ppm. The peak area integration at δH = 5.82 and 2.84 ppm was about 1:1, which shows that the grafting ratio of terephthalic acid to 5-hexenoic acid is 1:1.

[0066] Step 2: Dissolve a certain amount of POSS-1 in chloroform, then add 42g (0.28 mol) of 2-mercaptobenzoxazole and a certain amount of triethylamine, and synthesize the terminal benzoxazole POSS-2 molecule through the thiol-double bond click reaction. After the reaction is completed, the solvent is removed by rotary evaporation, and the reactive functionalized POSS-2 sizing agent molecule with the appearance of light yellow powder or yellow transparent oil is obtained by vacuum drying. The synthesized structure POSS-2 was confirmed by nuclear magnetic resonance ( 1H NMR) characterization confirmed that the peaks representing double bonds at δH (DMSO-d6) = 4.88, 5.13, 5.82 ppm disappeared, indicating that the reaction was successful and all double bonds were reacted. The structure Fourier infrared data FT-IR (KBr): v = 3303, 2929, 2858, 1692, 1538, 1461, 1094 cm -1 .

[0067] (2) Synthesis of POSS gel factor:

[0068] 378g (0.20mol) BOC-β-alanine was dissolved in 300mL DMF, and then 761g (1mol) HBTU and 298g (2.1mol) HOBt were added, and stirred for 5min in an ice-water bath to make it evenly mixed. Subsequently, 364g (3.6mol) N-methylmorpholine and 234g (0.2mol) OAS were added, and the reaction slowly warmed to room temperature and continued to react at room temperature for 24h. After the reaction was completed, the yellow-green solution obtained by the reaction was poured into 2000mL deionized water, and a white precipitate was obtained after slight stirring. The white precipitate was obtained by suction filtration, and the precipitate was washed with deionized water and acetonitrile and purified by column chromatography. The chromatographic stationary phase was 200-300 mesh silica gel, and the mobile phase was a mixed solvent of dichloromethane / methanol = 6 / 1. The obtained product POSS gel factor has a white crystalline appearance. δH(DMSO-d6)=7.79,6.74,3.01,2.96,2.44,1.54-1.39,1.25-1.40,0.59ppm. FTIR(ATR)v=3341,2985,2932,1690,1517,1372,1109cm -1 m / z (ESI-MS): [M+2Na]2+ theoretical value is 1147.7, measured value is 1146.9, the measured value is consistent with the theoretical value, proving that the structure of the obtained product is consistent with the designed structure. The structure of the Fourier infrared data FTIR (KBr): v = 3341, 2985, 2932, 1690, 1517, 1372, 1109cm -1 .

[0069] (3) PBO fiber sizing treatment:

[0070] 10g of POSS gel factor was dissolved in 1000mL of chloroform solvent, heated to 120°C, and 100g of reactive functionalized POSS-2 sizing agent molecules were added and mixed evenly to form a sol, which was a reactive functionalized POSS sizing agent. The reactive functionalized POSS sizing agent was cooled to 80°C, and the PBO fiber was immersed and sized. The treated PBO fiber was dried at 40°C.

[0071] Embodiment 3:

[0072] (1) Reactive functionalized POSS synthesis:

[0073] Step 1: Evenly mix 33g (0.28moL) of succinic acid and 32g (0.28moL) of 5-hexenoic acid in an ice bath, then add 110g (0.80moL) of 1-hydroxybenzotriazole (HOBT) and 290g (0.8moL) of benzotriazole-N,N,N',N'-tetramethyluronium hexafluorophosphate (HBTU), and add 150g (1.5moL) of N-methylmorpholine (NMM). After 30min, add 60g (0.07moL) of octa-aminopropyl POSS (OAS) hydrochloride. The reaction gradually returns to room temperature and stops after 24h. After the reaction is completed, the yellow solution obtained by the reaction is poured into 1000mL (0.50M) of citric acid aqueous solution, and a white precipitate is produced after mixing. The white precipitate was filtered out with a Buchner funnel, and the precipitate was washed three times with 500 mL of methanol, filtered out, and dried to obtain POSS-1 in the form of white powder or transparent oil. 1 H NMR) characterization confirmed that it was consistent with the design, δH(DMSO-d6) = 0.56, 1.51, 1.79, 2.16, 2.34, 2.42, 2.61, 3.41, 4.88, 5.13, 5.82, 12.18 ppm. The peak area integration at δH = 5.82 and 2.84 ppm was about 1:1, which showed that the grafting ratio of succinic acid to 5-hexenoic acid was 1:1.

[0074] Step 2: Dissolve a certain amount of POSS-1 in chloroform, then add 42g (0.28 mol) of 2-mercaptobenzoxazole and a certain amount of triethylamine, and synthesize the terminal benzoxazole POSS-2 molecule through the thiol-double bond click reaction. After the reaction is completed, the solvent is removed by rotary evaporation, and the reactive functionalized POSS-2 sizing agent molecule with the appearance of light yellow powder or yellow transparent oil is obtained by vacuum drying. The synthesized structure POSS-2 was confirmed by nuclear magnetic resonance ( 1 H NMR) characterization confirmed that the peaks representing double bonds at δH(DMSO-d6) = 4.88, 5.13, and 5.82 ppm disappeared, indicating that the reaction was complete and all double bonds were reacted. (2) Synthesis of POSS gel factor:

[0075] 462g (2mol) BOC-6-aminocaproic acid was dissolved in 300mL DMF, and then 761g (1mol) HBTU and 298g (2.1mol) HOBt were added, and stirred for 5min under an ice-water bath to make it uniformly mixed. Subsequently, 364g (3.6mol) N-methylmorpholine and 234g (0.2mol) OAS were added, and the reaction slowly warmed to room temperature and continued to react at room temperature for 24h. After the reaction was completed, the yellow-green solution obtained by the reaction was poured into 2000mL deionized water, and a white precipitate appeared after slight stirring. The precipitate obtained by centrifugation was washed with deionized water and acetonitrile and purified by column chromatography. The chromatographic stationary phase was 200-300 mesh silica gel, and the mobile phase was a mixed solvent of dichloromethane / methanol = 9 / 1. The product POSS gel factor obtained was white crystalline in appearance. δH(DMSO-d6)=7.77,6.76,3.01,2.88,2.04,1.54-1.39,1.27-1.39,1.20,0.59。FT-IR(ATR):v=3303,2925,2861,1680,1533,1465,1090。m / z(ESI-MS):[M+2Na]2+Theoretical value is 1315.7, and the measured value is 1316.7. The measured value is consistent with the theoretical value, which proves that the structure of the obtained product is consistent with the designed structure.

[0076] (3) PBO fiber sizing treatment:

[0077] 10g of POSS gel factor was dissolved in 1000mL of chloroform solvent, heated to 100°C, and 50g of reactive functionalized POSS-2 sizing agent molecules were added and mixed evenly to form a sol, which was a reactive functionalized POSS sizing agent. The reactive functionalized POSS sizing agent was cooled to 60°C, and the PBO fiber was immersed in the sizing treatment. The treated PBO fiber was dried at 40°C.

[0078] Embodiment 4:

[0079] (1) Reactive functionalized POSS synthesis:

[0080] Step 1: Evenly mix 46.5g (0.28moL) of terephthalic acid and 32g (0.28moL) of 5-hexenoic acid in an ice bath, then add 110g (0.80moL) of 1-hydroxybenzotriazole (HOBT) and 290g (0.80moL) of benzotriazole-N,N,N',N'-tetramethyluronium hexafluorophosphate (HBTU), and add 150g (1.50moL) of N-methylmorpholine (NMM). After 30min, add 60g (0.07moL) of octa-aminopropyl POSS (OAS) hydrochloride. The reaction gradually returns to room temperature and stops after 24h. After the reaction is completed, the yellow solution obtained by the reaction is poured into 1000mL (0.50M) of citric acid aqueous solution, and a white precipitate is generated after mixing. The white precipitate was filtered out with a Buchner funnel, and the precipitate was washed three times with 500 mL of methanol, filtered out, and dried to obtain POSS-1 in the form of white powder or transparent oil. 1 H NMR) characterization confirmed that it was consistent with the design, δH(DMSO-d6) = 0.56, 1.51, 1.79, 2.16, 2.34, 2.84, 3.41, 4.88, 5.13, 5.82, 8.06, 8.2112.17 ppm. The peak area integration at δH = 5.82 and 2.84 ppm was about 1:1, which shows that the grafting ratio of terephthalic acid to 5-hexenoic acid is 1:1.

[0081] Step 2: Dissolve a certain amount of POSS-1 in chloroform, then add 42g (0.28 mol) of 2-mercaptobenzoxazole and a certain amount of triethylamine, and synthesize the terminal benzoxazole POSS-2 molecule through the thiol-double bond click reaction. After the reaction is completed, the solvent is removed by rotary evaporation, and the reactive functionalized POSS-2 sizing agent molecule with the appearance of light yellow powder or yellow transparent oil is obtained by vacuum drying. The synthesized structure POSS-2 was confirmed by nuclear magnetic resonance ( 1 H NMR) characterization confirmed that the peaks representing double bonds at δH (DMSO-d6) = 4.88, 5.13, 5.82 ppm disappeared, indicating that the reaction was successful and all double bonds were reacted. The structure Fourier infrared data FT-IR (KBr): v = 3303, 2929, 2858, 1692, 1538, 1461, 1094 cm -1 .

[0082] (2) Synthesis of POSS gel factor:

[0083] 357g (1.0mol) CBZ-L-aspartame β-benzyl ester (Z-Asp-OH) was dissolved in 200mL DMF, and then 380g (0.50mol) HBTU and 149g (1.10mol) HOBt were added, and stirred for 5min under an ice-water bath to make it evenly mixed. Subsequently, 182g (1.80mol) N-methylmorpholine and 117g (0.10mol) POSS-OAS were added, and the reaction slowly warmed to room temperature and continued to react at room temperature for 24h. After the reaction was completed, the yellow-green solution obtained by the reaction was poured into 1000mL deionized water, and a white precipitate was obtained after slight stirring. A white precipitate was obtained after suction filtration with a Buchner funnel, and the precipitate was purified by column chromatography after washing with deionized water and acetonitrile. The chromatographic stationary phase was 200-300 mesh silica gel, and the mobile phase was a mixed solvent of dichloromethane / methanol = 9 / 1. The obtained product POSS gel factor had a white crystalline appearance. δH(DMSO-d6)=7.98,7.53,7.30,4.99,4.42,3.00,2.77,1.43,0.55. FTIR(KBr)v=3310,3070,2940,1740,1660,1280,1120,685,553,480cm -1 . m / z(ESI-MS):[M+2Na] 2+ The theoretical value is 1821, and the measured value is 1821. The measured value is consistent with the theoretical value. (MALDI-TOF): [M+Na] + The theoretical value is 3619.0, and the measured value is 3618.9, proving that the molecule was successfully synthesized.

[0084] (3) PBO fiber sizing treatment:

[0085] 10g of POSS gel factor was dissolved in 1000mL of solvent styrene, heated to 120℃ and 100g of reactive functionalized POSS-2 sizing agent molecules were added and mixed evenly to form a sol, which was a reactive functionalized POSS sizing agent. The reactive functionalized POSS sizing agent was cooled to 80℃ and the PBO fiber was soaked and sized. The treated PBO fiber was dried at 40℃. The synthesized structure POSS-2 was measured by nuclear magnetic resonance ( 1 H NMR) characterization confirmed that the peaks representing double bonds at δH(DMSO-d6)=4.88, 5.13, and 5.82 ppm disappeared, indicating that the reaction was successful and all double bonds were reacted.

[0086] Embodiment 5:

[0087] (1) Reactive functionalized POSS synthesis:

[0088] Step 1: Evenly mix 46.5g (0.28moL) of terephthalic acid and 32g (0.28moL) of 5-hexenoic acid in an ice bath, then add 110g (0.80moL) of 1-hydroxybenzotriazole (HOBT) and 290g (0.80moL) of benzotriazole-N,N,N',N'-tetramethyluronium hexafluorophosphate (HBTU), and add 150g (1.50moL) of N-methylmorpholine (NMM). After 30min, add 60g (0.07moL) of octa-aminopropyl POSS (OAS) hydrochloride. The reaction gradually returns to room temperature and stops after 24h. After the reaction is completed, the yellow solution obtained by the reaction is poured into 1000mL (0.50M) of citric acid aqueous solution, and a white precipitate is generated after mixing. The white precipitate was filtered out with a Buchner funnel, and the precipitate was washed three times with 500 mL of methanol, filtered out, and dried to obtain POSS-1 in the form of white powder or transparent oil. 1 H NMR) characterization confirmed that it was consistent with the design, δH(DMSO-d6) = 0.56, 1.51, 1.79, 2.16, 2.34, 2.84, 3.41, 4.88, 5.13, 5.82, 8.06, 8.2112.17 ppm. The peak area integration at δH = 5.82 and 2.84 ppm was about 1:1, which shows that the grafting ratio of terephthalic acid to 5-hexenoic acid is 1:1.

[0089] Step 2: Dissolve a certain amount of POSS-1 in chloroform, then add 42g (0.28 mol) of 2-mercaptobenzoxazole and a certain amount of triethylamine, and synthesize the terminal benzoxazole POSS-2 molecule through the thiol-double bond click reaction. After the reaction is completed, the solvent is removed by rotary evaporation, and the reactive functionalized POSS-2 sizing agent molecule with the appearance of light yellow powder or yellow transparent oil is obtained by vacuum drying. The synthesized structure POSS-2 was confirmed by nuclear magnetic resonance ( 1 H NMR) characterization confirmed that the peaks representing double bonds at δH(DMSO-d6)=4.88, 5.13, 5.82 ppm disappeared, indicating that the reaction was successful and all double bonds were reacted. (2) Synthesis of POSS gel factor:

[0090] 236g (0.60mol) (S)-2,6-di-tert-butoxycarbonylaminocaproic acid (BOC-Lys(BOC)-OH) was dissolved in 200mL N,N-dimethylformamide (DMF), and then 139g (1.36mmol) N-methylmorpholine (NMM) was added. A mixture of 144g (0.68mol) carbodiimide (EDCI) and 101g (0.75mol) 1-hydroxybenzotriazole (HOBT) was added under ice bath. After activation for 30min, 50g (0.043mol) POSS amino hydrochloride was added. The reaction was gradually warmed to room temperature and the reaction lasted for 24h. After the reaction was completed, a yellow solution was obtained, which was poured into 1000mL (0.50mol / L) of citric acid-water solution, and a white precipitate was produced after the two were mixed. The white precipitate was obtained by filtering with a Buchner funnel, and the white precipitate was washed with acetonitrile and purified by a chromatographic column. The stationary phase of the silica gel column is 200-300 mesh silica gel, and the mobile phase is a mixed solvent of dichloromethane / methanol with a volume ratio of 15:1. The obtained product POSS gel factor has a white crystalline appearance. δH(DMSO-d6)=7.74,6.70,6.36,3.79,2.99,2.83,1.54-1.39,1.25-1.40,0.52ppm. FTIR(KBr)v=3341,2985,2932,1690,1517,1372,1109cm -1 m / z (ESI-MS): [M+H+Na] / 2 The theoretical value is 1765.4, and the measured value is 1765.4. The measured value is consistent with the theoretical value, proving that the structure of the obtained product is consistent with the designed structure.

[0091] (3) PBO fiber sizing treatment:

[0092] 10g of POSS gel factor was dissolved in 1000mL of chloroform solvent, heated to 120°C, and 100g of reactive functionalized POSS-2 sizing agent molecules were added and mixed evenly to form a sol, which was a reactive functionalized POSS sizing agent. The reactive functionalized POSS sizing agent was cooled to 80°C, and the PBO fiber was immersed and sized. The treated PBO fiber was dried at 40°C.

[0093] After the surface of PBO fiber is treated with the reactive functional sizing agent prepared by the above method, the surface energy of the PBO fiber and the bonding strength with the resin matrix are greatly improved.

[0094] The test methods for various properties of the PBO fiber treated with the reactive functional sizing agent are as follows:

[0095] (1) Surface energy test

[0096] The Wilhelmy method was used to test the dynamic contact angle of PBO fibers. The fiber sample was vertically immersed in the test liquid at a certain speed and then pulled out of the liquid. The dynamic contact angle of the liquid on the fiber surface was calculated from the measured force change using a formula, and then the surface energy of the PBO fiber was calculated based on the obtained data. Two liquids were selected: deionized water (γ = 72.8 mNm -1 , γ d =21.8mNm -1 , γ p =51mNm -1 ) and ethylene glycol (γ=48mNm -1 , γ d =29mNm -1 , γ p =19mNm -1 ) is tested. During the test, the fiber is ensured to enter the liquid surface vertically, the immersion length is 5mm, and the speed is 0.05mm / s. The fiber advancing angle is the contact angle, which can be calculated from the mass difference of the fiber entering and leaving the liquid. The formula is:

[0097] Cosθ=mg / πdγ

[0098] Where, θ is the contact angle of the fiber (°), g is the acceleration of gravity, d is the diameter of the PBO fiber (μm), and γ is the surface tension of the test liquid (mNm -1 ).

[0099] By testing the dynamic contact angle of PBO fiber in different polar liquids, the surface energy of PBO fiber is calculated using the following formula:

[0100] γ l (1+Cosθ)=2(γ l p γ f p ) 1 / 2 +2(γ l d γ f d ) 1 / 2

[0101] γ f =γ f p +γ f d

[0102] Among them, γ l The surface energy of the test liquid (mNm -1 ), γ l p To test the polar component of liquid surface energy (mNm -1 ), γl d To test the dispersion component of liquid surface energy (mNm -1 ), γ f To test the fiber surface energy (mNm -1 ), γ f p To test the polar component of fiber surface energy (mNm -1 ), γ f d To test the dispersion component of fiber surface energy (mNm -1 ).

[0103] (2) Test of bonding strength between fiber and resin matrix

[0104] The microdroplet debonding method was used to test the bonding strength between PBO fiber and resin matrix. Select a single filament from the dried PBO fiber bundle and fix it on the test sample holder, and fix both ends with universal glue. Then prepare the resin glue, use a fine needle to dip a small amount of resin glue and evenly apply it on the surface of the PBO fiber monofilament. The resin forms droplets on the fiber surface under the action of surface tension. Place the sample holder in an oven for curing, and cool to room temperature to obtain a droplet test sample. During the test, select a resin droplet of appropriate size (60μm-80μm), clamp it with a knife blade, and pull the fiber axially at a speed of 0.5μm, so that the interface between the fiber and the resin is subjected to shear stress. When the shear stress reaches the maximum, the resin droplet and the fiber debond. The bonding strength between the fiber and the resin matrix, that is, the interfacial shear strength, can be calculated by the following formula:

[0105]

[0106] Among them, F max is the maximum load when the resin droplet is debonded from the fiber (N), d is the diameter of the PBO fiber monofilament (m), and l is the fiber length embedded by the resin droplet (m)

[0107] The surface energy test results of the above embodiments are shown in the following table:

[0108] Table 1. Surface energy test results of various examples

[0109]

[0110] The test results of the bonding strength between the fibers and the resin matrix in the above embodiments are shown in the following table:

[0111] Table 2. Test results of bonding strength between fiber and resin matrix in various examples

[0112]

[0113] The performance test results of the products in the above embodiments show that the PBO fibers after the gel-assisted surface treatment of the present invention have good bonding performance with the resin matrix.

[0114] The above are only embodiments of the present invention, and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A gel-assisted PBO fiber surface non-destructive treatment method, characterized in that: The following steps are involved: (1) Preparation of reactive functionalized POSS, specifically including: 1.1): In an ice bath, graft 1 and graft 2 are mixed in a ratio of 4:4-2:6, and then condensation reagents 1-hydroxybenzotriazole and benzotriazole-N,N,N',N'-tetramethyluronium hexafluorophosphate are added, and N-methylmorpholine is added as an acid binding agent, and then a POSS derivative is added. The reaction is continued for 18-30 hours and then stopped. After the reaction is completed, POSS-1 is obtained by post-treatment; The grafted substance 1 is at least one of succinic acid, glutaric acid, terephthalic acid, isophthalic acid, furandicarboxylic acid, adipic acid, sebacic acid, and suberic acid; The grafted substance 2 is at least one of 5-hexenoic acid, 2-methyl-4-pentenoic acid, 4-pentenoic acid, 6-heptenoic acid, 7-octenoic acid, 8-nonenoic acid, and 9-decenoic acid; The POSS derivative is octa-aminopropyl POSS hydrochloride, γ-glycidyloxysilylpropyl POSS, octavinyl-POSS or octachloropropyl silsesquioxane; 1.2): POSS-1 was dissolved in chloroform, and then grafted material 3 and triethylamine were added to synthesize terminal benzoxazole-modified POSS-2 molecules through thiol-double bond click reaction. After the reaction, the solvent was removed by rotary evaporation, and the reactive functionalized POSS was obtained after vacuum drying; The grafted substance 3 is 2-mercaptobenzoxazole, 5-methoxybenzoxazole-2-thiol or 5-chloro-2-mercaptobenzoxazole; (2) Preparing a POSS gel factor, specifically comprising: 2.1): (S)-2, 6-di-tert-butoxycarbonylaminocaproic acid is dissolved in N,N-dimethylformamide, then N-methylmorpholine is added, and a mixture of carbodiimide and 1-hydroxybenzotriazole is added under ice bath; 2.2): After activation for 20-40 minutes, add POSS amino hydrochloride, gradually raise the reaction temperature to 15-35°C, and continue the reaction for 16-30 hours; 2.3): After the reaction is completed, a yellow solution is obtained, and the yellow solution is poured into a citric acid-water solution. After the two are mixed, a white precipitate is generated, and the white precipitate is post-treated to obtain a POSS gel factor; (3) Sizing of PBO fibers by gel-assisted technology, including: 3.1): Dissolve the POSS gel factor in a solvent, heat to 100-140°C, add the reactive functionalized POSS and mix evenly to form a sol, which is the reactive functionalized POSS sizing agent; 3.2): The reactive functionalized POSS sizing agent is cooled to 80°C to 40°C, and the PBO fiber is immersed in the sizing agent.

2. The gel-assisted PBO fiber surface non-destructive treatment method according to claim 1, characterized in that: In step 1.1), post-processing includes: The yellow solution obtained after the reaction is completed is poured into a citric acid aqueous solution, and a white precipitate is generated after mixing. The white precipitate is obtained by suction filtration. The precipitate is washed with methanol, suction filtered, and dried to obtain POSS-1.

3. The gel-assisted PBO fiber surface non-destructive treatment method according to claim 1, characterized in that: In step 2.3), the post-processing includes: The white precipitate was washed with acetonitrile and purified by chromatography to obtain the product POSS gel factor.

4. The gel-assisted PBO fiber surface non-destructive treatment method according to claim 1, characterized in that: In step 3.1), the reactive functionalized POSS sizing agent adopts the following components in parts by weight: 85-95 parts of solvent; Reactive functionalized POSS 5-10 parts; POSS gel factor 0.5-5 parts.

5. The gel-assisted PBO fiber surface non-destructive treatment method according to claim 1, characterized in that: In step 3.1), the mixture is heated to 110-130°C and reactive functionalized POSS is added and mixed to form a sol.

Citation Information

Patent Citations

  • Method for enhancing ultraviolet resistance stability of PBO (poly-p-phenylenebenzobisthiazole) fibers by depositing (POSS (polyhedral oligomeric silsesquioxane) / TiO2)n films on surfaces

    CN102634976A

  • A benzoxazole ionic compound and a PBO fiber emulsion sizing agent containing the compound, and a method for preparing the same.

    CN111825696B

  • PBO fiber sizing agent containing benzoxazole diamine compatilizer and application of PBO fiber sizing agent

    CN112760972A

  • Preparation method of POSS modified PBO polymer

    CN104292461A

  • Dendritic gelator and preparation and application thereof

    CN107353406A